Infantile myofibroma: A report of two cases with differential diagnoses - Soumya Dey; Bappa Mandal; Uttara Chatterjee; Suchandra Mukherjee (Wolters Kluwer Medknow Publications, 2022)
Infantile myofibromas (IMs) are benign soft-tissue tumors of children. They are of fibroblastic-myofibroblastic origin and show considerable morphological overlap with other spindle cell neoplasms. Here, we present two cases of solitary myofibromas, one in a neonate and one in a 2-year-old girl. A 2-day-old girl presented with severe respiratory distress and died during intubation. At autopsy, a myofibroma involving the oropharynx with extension up to the larynx was noted. Second case was a 2-year-girl with a myofibroma in the hard palate. IM must be differentiated from other benign and malignant spindle cell tumors of infancy and childhood. Oropharyngeal myofibroma should be considered in the differentials of neonatal respiratory distress.